Hong Kong's Indigenous Democracy: Origins, Evolution and Contentions - Lo, Sonny Shiu-Hing (Palgrave Macmillan, 2020)
This book is a unique contribution to the study of democratization in Hong Kong, with chapters including the legal tradition in Hong Kong, the features of Hong Kong's indigenous democracy, the 2014 Umbrella Movement, and the evolution of the Chief Executive election.